PEMANFAATAN BUAH PISANG SEBAGAI BAHAN BAKU TEPUNG - Dwi Nur Rahmawati; Weli Sentiya Tanjung; Aliya Dara Sufi; Saodin (STIE Muhammadiyah Kalianda, 2024)
In Suak village, Sidomulyo sub-district, there was a lack of knowledge about diversification of processed banana fruits, which resulted in spoilage of banana fruits that were not marketed due to the abundance of bananas in Suak village. Therefore, Suak villagers innovated to process banana fruit into banana flour. The purpose of this community service is to provide information on the renewal of good quality banana flour processing in order to maximize the local potential in Suak area. The method used is planning first, namely situation analysis using data and information obtained from Suak Village, then compiling the data obtained to be used as a research article. The results of this service will be a source of information